IDEOLOGICAL DECLINE AND HUMAN STRUGGLE IN KAKKANADAN’S USHNAMEGHALA - S. Jayan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This article explores Kakkanadan’s Ushnameghala as a literary portrayal of revolutionary consciousness and class struggle in post-independence Kerala. Through the life of the protagonist Shivan, the novel reveals the complex realities faced by revolutionaries, balancing intense political commitment with personal and familial conflicts. The narrative highlights the fervour of armed struggle as a catalyst for social change, while also chronicling the disillusionment that arises from the decline of the communist movement and its ideological betrayals. Through illustrating the conflicts between traditional and modern communist ideologies and the conversion of revolutionary fervour into political power struggles, Ushnameghala provides a critical analysis of the deterioration of revolutionary principles and the difficulties in maintaining group goals for social justice.